A cross-sectional analysis of women’s sports perceptions and athletic engagement - Jay Carlo Bagayas; Leonard John Carrillo (spdfharmony.com, 2026)
Background: Perceptions of women’s participation in sport may shape how strongly students engage in athletic activities, yet evidence from Philippine higher education settings remains limited. Aims: To examine the association between female students’ perceptions of women’s sports participation (PWSPI) and overall athletic engagement (AE) and its dimensions in confidence (AEC), dedication (AED), enthusiasm (AEE), and vigor (AEV). Methods: A quantitative, cross‑sectional correlational survey was administered to N = 293 female students enrolled in PATHFIT service Physical Education courses across multiple Higher Education Institutions in Mindanao, Philippines. Perceptions were assessed using the Perception of Women’s Sports Participation Inventory (PWSPI) and engagement with the Athlete Engagement Questionnaire (AEQ). Given Likert‑type responses and non‑normal distributions, Spearman rank‑order correlations (two‑tailed α = .05) with 95% bootstrap confidence intervals were used to quantify associations. Result: PWSPI was positively and significantly associated with overall athletic engagement (ρ = .169, p = .004, 95% CI [.055, .278]). At the subscale level, dedication (AED), enthusiasm (AEE), and vigor (AEV) each showed small, significant positive associations with PWSPI, whereas confidence (AEC) did not reach statistical significance. Conclusion: Perceptions of women’s sports participation are associated with modestly higher athletic engagement, particularly in motivational and energetic facets (dedication, enthusiasm, vigor). Cultivating gender‑affirming climates while embedding targeted efficacy‑building strategies (e.g., mastery experiences and feedback) may help translate supportive perceptions into stronger confidence and sustained participation.